English adjectives of very similar meaning used in combination: an exploratory, corpus-aided study - Stephen James Coffey (Lexis: Journal in English Lexicology)
This article reports on research into the phenomenon whereby English adjectives of very similar meaning are sometimes used in combination, either as an uncoordinated sequence (as in ‘simple straightforward’) or as a coordinated pair (as in ‘dull and monotonous’). One of the preliminary goals of the research is to identify areas of meaning in which such adjective combinations typically occur. In order to find relevant examples, the British National Corpus was used as a source of textual material to work from. The article explains the methodology employed to locate phrasal items of interest, which partly involved using the Phrases in English (PIE) database. Details are presented of ten specific areas of descriptive meaning where a number of different adjective combinations were found, as well as a set of emphasizing and/or intensifying adjectives with similar characteristics. Possible reasons are suggested for the doubling-up of meaning, and the relevance of the phenomenon to synonym studies is discussed. More than 200 corpus examples are included.